2012
DOI: 10.4172/2155-9864.1000121
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplastic Syndrome: An Egyptian Experience

Abstract: Background: Myelodysplastic syndromes (MDS) incidence is unclear because of historical lack of populationbased registration and possibly because of under diagnosis. Purpose:To present some retrospective data on the epidemiology of Myelodysplastic syndrome (MDS) in Egypt, as reflected by a single centre which is the largest tertiary referral center of Haematology in Egypt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
5
1
0
Order By: Relevance
“…In the present study, male to female ratio was 1.4:1, which is consistent with reports from European and Asian regions [17]. The mean age was 56 years and the median was 57.5 years, which was in line with the mean age 55 years that was previously reported in Egyptian patients with MDS [18], and comparable with median age 60 years in Tunisian [19] and 59 years in Pakistani patients [17]. However, the age was lower (67 years) than that recorded in USA patients [20], and higher (45 years) than that reported in Chinese [21] and in Indian (42 years) patients [22].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, male to female ratio was 1.4:1, which is consistent with reports from European and Asian regions [17]. The mean age was 56 years and the median was 57.5 years, which was in line with the mean age 55 years that was previously reported in Egyptian patients with MDS [18], and comparable with median age 60 years in Tunisian [19] and 59 years in Pakistani patients [17]. However, the age was lower (67 years) than that recorded in USA patients [20], and higher (45 years) than that reported in Chinese [21] and in Indian (42 years) patients [22].…”
Section: Discussionsupporting
confidence: 93%
“…According to WHO 2016, MDS-MLD in our study was the most frequent reported primary MDS subtype (38%) followed by MDS-SLD (RA) (22%) which was in agreement with previous reports from Egyptian MDS patients [18] while MDS-MLD was the most frequent subtype among German patients (27.6%) followed by MDS-EB-II (20.6%) [24], in US patients (32.2%) followed by MDS-EB-I (19.7%) [20], in Chinese patients (44%) followed by MDS-EB-I (19%) [21], and in Pakistani patients (52.1%) followed by MDS-EB-II (23.9%) [17]. This finding was in contrast with Indian primary MDS patients as MDS-SLD was the most frequent MDS subtype (37.5%) followed by MDS-EB-I (17.5%) [22].…”
Section: Discussionsupporting
confidence: 92%
“…According to WHO 2016, MDS-MLD in our study was the most frequent reported primary MDS subtype (38%) followed by MDS-SLD (RA) (22%) which was in agreement with previous reports from Egyptian MDS patients [18] while MDS-MLD was the most frequent subtype among German patients (27.6%) followed by MDS-EB-II (20.6%) [24] , in US patients (32.2%) followed by MDS-EB-I (19.7%) [20] , in Chinese patients (44%) followed by MDS-EB-I (19%) [21] , and in Pakistani patients (52.1%) followed by MDS-EB-II (23.9%) [17] . This finding was in contrast with Indian primary MDS patients as MDS-SLD was the most frequent MDS subtype (37.5%) followed by MDS-EB-I (17.5%) [22] .…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, male to female ratio was 1.4:1, which is consistent with reports from European and Asian regions [17] . The mean age was 56 years and the median was 57.5 years, which was in line with the mean age 55 years that was previously reported in Egyptian patients with MDS [18] , and comparable with median age 60 years in Tunisian [19] and 59 years in Pakistani patients [17] . However, the age was lower (67 years) than that recorded in USA patients [20] , and higher (45 years) than that reported in Chinese [21] and in Indian (42 years) patients [22] .…”
Section: Discussionsupporting
confidence: 90%
“…This is therefore likely to represent an epidemiological transition as there was a 24% increase in MDS cases over 14 years, reflecting an ageing population, whose life expectancy has increased from 73 years in 2005 to 76.5 in 2017 [28]. Moreover, the age of our MDS patients is higher than in Tunisia (mean age=55 years) [26], Morocco (mean age=66 tears) [27], Egypt (mean age=55 years) [29] or Pakistan (mean age=58 years) [30], but still lower than in Greece (mean age=73,1 years) [25] or in Europe (mean age=71 years) [31][32]. In our study, a slight female predominance (ratio F/M=1.11) was found, particularly in the age group between 65 and 70 years (ratio F/M=1,17), as well as in Egypt (ratio=1,3), which differs from the slight male predominance generally reported in western countries.…”
Section: Figure 2b Overall Survival Stratified By Mds Typementioning
confidence: 99%